Leveraging modern DNA assembly techniques for rapid, markerless genome modification - Tikh, Ilya B (Biol Methods Protoc, 2016)
The ability to alter the genomic material of a prokaryotic cell is necessary for experiments designed to define the biology of the organism. In addition, the production of biomolecules may be significantly improved by application of engineered prokaryotic host cells. Furthermore, in the age of synthetic biology, speed and efficiency are key factors when choosing a method for genome alteration. To address these needs, we have developed a method for modification of the Escherichia coli genome named FAST-GE for Fast Assembly-mediated Scarless Targeted Genome Editing. Traditional cloning steps such as plasmid transformation, propagation and isolation were eliminated. Instead, we developed a DNA assembly-based approach for generating scarless strain modifications, which may include point mutations, deletions and gene replacements, within 48 h after the receipt of polymerase chain reaction primers. The protocol uses established, but optimized, genome modification components such as I-SceI endonuclease to improve recombination efficiency and SacB as a counter-selection mechanism. All DNA-encoded components are assembled into a single allele-exchange vector named pDEL. We were able to rapidly modify the genomes of both E. coli B and K-12 strains with high efficiency. In principle, the method may be applied to other prokaryotic organisms capable of circular dsDNA uptake and homologous recombination.